Self-representation: A review on Selfie Photos in Social Media According to Goffman's Dramaturgical Theory - Keyhan Valinejad (پیکره)
Introduction: Presenting a selfie photo as a form of expressing self-identity has turned out a common behavior. Showing our selfie photos in various environments, decorative spaces, and situations, with different attitudes, whether in familiar or unfamiliar groups of people, is built on structures that, despite our desire to present a perfect appearance of ourselves, interactively affect our identity. Partial or major self-censorship of our characteristics that are either undesirable to us or there is no reason to present them arises from being aware of this fact. A huge part of liking or disliking our selfies is the outcome of receiving likes and dislikes from our addressed followers. This research aims to find the reasons for presenting some kind of selfie images on social media based on the theory of 'Presentation of Self' by Erving Goffman or Goffman's Dramaturgical Theory to understand the motivations behind these behaviors in more detail.Research Method: First, the theory of ‘Presentation of Self’ by Erving Goffman has been described by adopting a descriptive method; and then by explaining the selfie photos, it has been tried to analyze the implications of this theory to this kind of photography in social media. In this research, by using a qualitative method, and relying on several case studies acquired by the Instagram photo-sharing network, the implications of Goffman's theory have been explained. The photos reviewed in this research (10 photos) were selected out of a hundred photos in user profiles as the research statistical population, based on a comparative classification, and relevant to the research topic. To describe and analyze the theoretical subjects, several original research articles and e-books were adopted.Findings: The individual and social identical patterns and the attempt to present a proper selfie in social media are more frequent, flexible, and even interactive compared to the real world due to the self-management nature of these environments.Conclusion: Social media has brought a new public space that enables multiple identities. According to Goffman's theory, uploading a selfie photo can be interpreted as a play, in which the subject consciously manipulates his/her characteristics even in a slight manner. Besides this, by masking/unmasking a personality, the person expresses the kind of characteristics that respond to his/her desire to present an ideal image to acquire social acceptance.